Prognostic differences between persistent HFrEF and HFrecEF following acute myocardial infarction - Jeong Yoon Jang; Jae Myoung Lee; Yujin Shin; Yong-Lee Kim; Gain Yu; Jae Seok Bae; Yun-Ho Cho; Choong Hwan Kwak; Min Gyu Kang; Kye-Hwan Kim; Jeong Rang Park; Jin-Yong Hwang; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) often leads to heart failure with reduced ejection fraction (HFrEF), with some patients showing recovery of left ventricular ejection fraction (HFrecEF) over time. This study aimed to evaluate the prognostic differences between persistent HFrEF and HFrecEF.MethodsThis prospective cohort study included AMI patients with reduced LVEF (<40%) at admission. LVEF was reassessed one month later to classify patients into persistent HFrEF (LVEF <40%) or HFrecEF, defined as follow-up LVEF >40% with an absolute increase of ≥10% from baseline, in accordance with recent consensus definitions. Outcomes included cardiovascular mortality and/or rehospitalization for heart failure. Predictors of LVEF recovery were also analyzed.ResultsOf the 679 patients analyzed, 373 (55%) had persistent HFrEF, while 306 (45%) transitioned to HFrecEF. Patients with HFrecEF were younger, had fewer comorbidities, and were more likely to receive renin-angiotensin system (RAS) inhibitors and β-blockers.Cardiovascular mortality was significantly lower in the HFrecEF group (3.3% vs. 8.3%; adjusted HR 0.37, 95% CI: 0.18–0.77, p = 0.007), as was the rate of heart failure rehospitalization (6.2% vs. 10.2%; adjusted HR 0.60, 95% CI: 0.35–1.05, p = 0.074). Independent predictors of LVEF recovery included younger age, beta-blocker use, and RAS inhibitor use.ConclusionThis study emphasizes the critical role of transitioning from persistent HFrEF to HFrecEF in improving clinical outcomes for AMI patients. Tailored management approaches, combined with routine echocardiographic monitoring and adherence to optimal medical therapy, are essential for optimizing patient care and long-term prognosis.